Gasoline pricing, taxation and asymmetry: The case of Turkey - Özgür Bor; Mustafa İsmihan (Turkish Economic Association, 2013)
This study analyzes the role of tax policy in gasoline prices in Turkey by utilizing time series techniques. It provides and compares empirical results by using daily gasoline prices between January 2005 and July 2012, with and without the effect of taxation. Our results, based on the standard asymmetric error-correction model, indicate no evidence of asymmetry in retail gasoline prices, which implies that the government does not benefit from the adjustment of gasoline prices through taxation. However, one can miss the big picture in gasoline pricing by concentrating only on the short term price adjustment dynamics via error-correction models. Therefore, we analyzed the long-run relationships between crude oil and gasoline prices with and without taxes. The results indicate that Turkish government succeeded at implicitly imposing an exceptionally high tax burden on gasoline (about 70%) over the longer term by adjusting non-salient excise tax amounts on gasoline and benefited from the resultant tax revenues as means of public finance.
Keywords: 330; gasoline pricing; taxation; asymmetry; Benzinpreis; Steuerpolitik; Kointegration; Schätzung; Türkei